Simultaneous linear circular functional relationship model - Hussin, A.G.; Zubairi, Y.Z.; Hassan, S.F. (2008)
This paper proposed the statistical model on how to look at the relationship between several circular variables which area subject to measurement errors. Maximum likelihood estimation of parameters has been obtained iteratively assuming the ratio of concentration parameters are known and by choosing suitable initial values. The variance and covariance have also been derived using the Fisher information matrix. The model was applied to the Malaysian wind direction recorded at various levels.